DAMPAK MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GEYO TAMA JAYA KOTA DEPOK - Abdul Azis; Abdul Rahman Safiih (Jurnal Menara, 2025)
The purpose of this research is to determine the extent of the impact of Work Motivation and Work Discipline on Employee Performance both partially and simultaneously. This research uses a quantitative approach, with a total population of 51 employees. The data collection techniques used are primary data, namely observation, interviews, and questionnaires. The data analysis method used is multiple linear regression using SPSS version 26. The regression equation is Y = 3.011 + 0.434 X1 + 0.526 X2, (F test) on the Work Motivation variable (X1) and Work Discipline variable (X2) shows a calculated f value > f table value, which is 34.842 > 2.800, and has a significance value of 0.000 < 0.05. Therefore, it can be concluded that the Work Motivation variable (X1) and Work Discipline variable (X2) together (simultaneously) have a significant impact on Employee Performance variable (Y) at PT Geyo Tama in Depok City.